ASPEK HAK ASASI MANUSIA DALAM PENGADAAN TANAH - Dian Aries Mujiburohman (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
The paper is aimed at studying the land acquisition as seen from the human right perspective. The values of humanright should be the basis of the development as this is closely related to human right. Nilai-nilai dasar HAM harus mendasaripembangunan, karena terkait erat antara pembangunan dan HAM. The society, having been affected by the development, shouldget a more prosperous life than the condition prior to the development process or at least they have similar condition as comparedto the situation before the land acquisition process takes place. . The activity should also protect people’s prosperity so that theydo not get poorer.. Some consideration should taken in land acquisition. First, the loss of income due to the loss or decrease oflands. Second, the loss of jobs both temporary or permanent. Third, social unhappiness due to the loss of kinship relation. Forth,the loss of nucleus family relation. This might affect the socio-seconomic statu inc ome.Key words: Human right, public inetrest, land acquisition.